2022
DOI: 10.3390/ijms23031142
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel-Induced Epidermal Alterations: An In Vitro Preclinical Assessment in Primary Keratinocytes and in a 3D Epidermis Model

Abstract: Paclitaxel is a microtubule-stabilizing chemotherapeutic agent approved for the treatment of ovarian, non-small cell lung, head, neck, and breast cancers. Despite its beneficial effects on cancer and widespread use, paclitaxel also damages healthy tissues, including the skin. However, the mechanisms that drive these skin adverse events are not clearly understood. In the present study, we demonstrated, by using both primary epidermal keratinocytes (NHEK) and a 3D epidermis model, that paclitaxel impairs differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Paclitaxel and docetaxel, taxane anticancer agents, induce tumor cytotoxicity, as well as anti‐angiogenetic reactions 10–15 . Both paclitaxel and docetaxel increase the production of reactive oxygen species (ROS), 10–12 leading to reduced endothelial tube formation in dermal microvascular endothelial cells (HDMECs) 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Paclitaxel and docetaxel, taxane anticancer agents, induce tumor cytotoxicity, as well as anti‐angiogenetic reactions 10–15 . Both paclitaxel and docetaxel increase the production of reactive oxygen species (ROS), 10–12 leading to reduced endothelial tube formation in dermal microvascular endothelial cells (HDMECs) 10 .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, both the activation of NF-kB that plays an important role in controlling cell survival and apoptosis and the consequent release of proinflammatory cytokines, such as IL-8, can be considered the bridge between inflammation, cancer and oxidative stress [ 59 , 60 , 61 ]. It has already been assessed, in the context of chemoprevention, that the redox-sensitive transcription factors NF-κB and IL-8 are inflammatory signaling mediators involved in oxidative stress either in human respiratory epithelial cells or in cancer epidermal alterations [ 62 , 63 ]. A recent study performed both with primary epidermal keratinocytes and in a 3D epidermis model showed that a chemotherapeutic agent, also approved for the treatment of NSCLC, induced an increased rate of oxidative stress, inflammation and apoptosis via the upregulation of both NF-κB and IL-8 expression [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has already been assessed, in the context of chemoprevention, that the redox-sensitive transcription factors NF-κB and IL-8 are inflammatory signaling mediators involved in oxidative stress either in human respiratory epithelial cells or in cancer epidermal alterations [ 62 , 63 ]. A recent study performed both with primary epidermal keratinocytes and in a 3D epidermis model showed that a chemotherapeutic agent, also approved for the treatment of NSCLC, induced an increased rate of oxidative stress, inflammation and apoptosis via the upregulation of both NF-κB and IL-8 expression [ 62 ]. Furthermore, other studies assessed that IL-8 expression correlated with ROS production, with ROS-induced mitochondrial damage and with the pro-apoptotic activity of chemopreventive agents, by demonstrating an increased expression of IL-8 in both human breast cancer and neuroblastoma cell [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that TLR4 is involved in mediating inflammation and immunity (36) and in regulating tumorigenesis and tumor progression (37). For example, TLR4 may promote the immune escape of human lung cancer cells and support ovarian cancer progression (38,39). Knockdown of TLR4 has been reported to inhibit the growth of human NSCLC cancer cells (40).…”
Section: Trim44 Is Positively Correlated With Tlr4 At the Mrna And Pr...mentioning
confidence: 99%